Determination of Pollutant Index (PI) for Assessing the Quality of Groundwater in the Area of Sidoarjo Mud (LUSI) Sidoarjo, East Java, Indonesia - Ilham Putra Adiyaksa; Oleg G. Savichev (Jurnal Sumberdaya Alam dan Lingkungan, 2023)
Sidoarjo mud (well known as LUSI) have been occurred since 2006 in Sidoarjo, East Java, Indonesia and gives many impacts to many aspects, as well as environment and water quality condition. One of the major concerns is water quality problem, especially in this current situation in 2022 since clean water still needed by local people and groundwater is the main water source for many local people in this area. Our previous study has carried out to assess the ecological and geochemical conditions of groundwater in the area around Sidoarjo mud in 2022. In this study, by using Pollutant Index (PI) calculation, the water quality classification will be determined from several samples and parameters in various places, including Tanggulangin, and Porong, Sidoarjo, East Java. From the calculation result, based on Pollution Index (PI) value, water in Tanggulangin is categorized as good water (clean water), while water in Porong is categorized as good water (clean) as well for sample B3, and the rest is categorized as lightly polluted water with sample B5 as the most contaminated. Groundwater in the area near to Sidoarjo mud is contaminated by NO2-, Mn, and Hg.